2017
DOI: 10.1103/physrevlett.119.077203
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Curvature-Induced Anisotropy in Thin Ferromagnetic Films

Abstract: We investigate the effect of large curvature and dipolar energy in thin ferromagnetic films with periodically modulated top and bottom surfaces on magnetization behavior. We predict that the dipolar interaction and surface curvature can produce perpendicular anisotropy which can be controlled by engineering special types of periodic surface structures. Similar effects can be achieved by a significant surface roughness in the film. We demonstrate that, in general, the anisotropy can point in an arbitrary direct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Accessing spin textures of geometrically curved magnetic thin films 39 , 41 44 , hollow cylinders 37 , 40 , 45 50 and wires 35 , 51 54 has become now a dynamic research field 23 , 55 . In our work, we performed a detailed study of the interplay between the intrinsic and extrinsic chiral interactions of 3D curvilinear objects within a 1D anisotropic Heisenberg magnet with intrinsic DMI.…”
Section: Introductionmentioning
confidence: 99%
“…Accessing spin textures of geometrically curved magnetic thin films 39 , 41 44 , hollow cylinders 37 , 40 , 45 50 and wires 35 , 51 54 has become now a dynamic research field 23 , 55 . In our work, we performed a detailed study of the interplay between the intrinsic and extrinsic chiral interactions of 3D curvilinear objects within a 1D anisotropic Heisenberg magnet with intrinsic DMI.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Recent research has shown that by engineering the surface, perpendicular or other types of magnetic anisotropy can be achieved in ultrathin magnetic films. [33] In our phase change heterostructure, the lattice variation in the specific plane is quite large, which could lead to some periodic bending and spin reorientation of the NiFe film at the interface. [34] Assuming that it mainly affects the domain wall motion, the mechanism can be understood through a strain-induced anisotropy change.…”
Section: Strain Analysis and Mechanism Explanationmentioning
confidence: 92%
“…Based on the understanding that the magnetism modulation is mainly due to the interfacial strain, we then focus on the origin of the magnetism modulation caused by interfacial strain during the phase change . Recent research has shown that by engineering the surface, perpendicular or other types of magnetic anisotropy can be achieved in ultrathin magnetic films . In our phase change heterostructure, the lattice variation in the specific plane is quite large, which could lead to some periodic bending and spin reorientation of the NiFe film at the interface .…”
Section: Strain Analysis and Mechanism Explanationmentioning
confidence: 99%
“…[ 64,65 ] The magnetic moments on curved surfaces defined by simple smooth functions f ( x,y ) can produce a magnetic anisotropy axis along any direction because of the long range dipolar interaction. [ 66,67 ] This global surface anisotropy arising from periodic topography can compensate the fluctuation of magnetizations. Confinement along the normal direction of a curved space usually changes the equation of motion of the particles, leads to the quantization of the electronic states, and may induce a curvature‐controllable geometric potentials, which is related to mean curvature and Gaussian curvature.…”
Section: Low Dimensional Theory For Magnetizationmentioning
confidence: 99%